Validation of an instrument to comply with institutional measures on tuberculosis infection control - Ortiz Rojas, Helen johana; García-Perdomo, Herney Andrés (Horizonte Sanitario, 2020)
ABSTRACT Objective: To assess an instrument’s psychometric properties to evaluate compliance with institutional tuberculosis infection control measures of Healthcare Providers in the city of Cali. Methods: A cross-sectional study (psychometric type, instrument validation). The development of instrument considered sections from the Guidelines for the preventing of transmission of Mycobacterium tuberculosis in health care settings (CDC), Guidelines for implementation of infection control of tuberculosis in the Americas and Evaluation Control Tools for Hospital-Acquired Infections. The construction of final instrument was carried out with the support of seven experts according to Delphi method, obtaining an instrument comprising three domains and a final number of 65 questions; each item was evaluated, usefulness, format, and validity of the instrument. Contents were assessed with the Aiken coefficient and reliability with Bangdiwala concordance coefficient. R version 3.2.0 application was used. Results: The instrument was made up by 65 items referring to questions regarding administrative, environmental and respiratory measures. It holds acceptable psychometric properties, including good internal structure and suitable reliability. Conclusions: A valid and reliable instrument was obtained to evaluate compliance with institutional measures on tuberculosis infection control in Healthcare Institutions in the city of Cali. Key Words: Tuberculosis; Validation Studies; Delphi Technique. RESUMEN Objetivo: El estudio tuvo como objetivo construir y establecer las propiedades psicométricas de un instrumento para evaluar el cumplimiento de las medidas institucionales de control de infecciones para la tuberculosis en las Instituciones Prestadoras de Salud de la ciudad de Cali. Métodos: El estudio fue de corte transversal (tipo psicométrico, validación de un instrumento). El desarrollo del instrumento consideró secciones de las Guidelines for the preventing of transmission of Mycobacterium tuberculosis in health care settings (CDC), Guidelines for implementation of infecti